Parenting Patterns Work in Developing Moral and Religious Values for Children Aged 5-6 at RA Bustanul Ulum Jayasakti Tuha Children, Central Lampung - Iffah Mu'arifah; Muhammad Yusuf; Ferdian Utama; Agus Setiawan; Leli Fertiliana Dea (International Journal on Advanced Science, Education, and Religion, 2024)
The aim of this research is to describe and determine the parenting patterns of parents working with a permissive method in developing the religious moral values of children aged 5-6 in RA Bustanul Ulum Jayasakti, Anak Tuha District, Central Lampung 2023-2024. This research is field research with a qualitative descriptive approach using the case study method. This research concluded that the parenting style applied by working parents mostly uses a mixed parenting pattern of democratic and permissive parenting, a parenting pattern that frees children to carry out activities, but parents still supervise and provide direction. Religious moral values should be instilled in children from an early age, even though children cannot yet understand what is being taught, as parents you must be diligent in educating your children, especially in matters of morals and religion. Busy parents to work, parents are less than optimal in educating their children, this lack of maximum results has an impact significant. Parents who have sufficient knowledge in educating, their children's religious morals are able to develop well, such as being easy to manage, being polite to older people and being disciplined, parents think that Children aged 5-6 are still too young to be taught and required to obey the rules with discipline and firmness towards children, so that children do not know their obligations, rules and good habits such as praying, reciting the Koran, speaking well, forgiving which must be done every day and Children will imitate their parents' behavior Everyday life often gets angry, making children prone to it argue and do not want to listen Keywords: Parenting Style, Working Parents, Moral Values and Religion